Performance Investigation of a High Data Rate Mode Division Multiplexed-Free Space Optics Link Under Harsh Weather Conditions - Singh, Mehtab; Pottoo, Sahil Nazir; Suvidhi,; Dewra, Sanjeev; Rishabh,; Grover, Amit; Manikandan, A.; Sheetal, Anu (Frontiers in Physics, 2021)
The requirement of high data rate information transmission is rising exponentially for supporting different services including social networking, web streaming, and biomedical sensor data transmission. Such services required high channel bandwidth with secure information transmission and immunity to electromagnetic interference. Radio over free space optics (RoFSO) is witnessed as a promising technological solution to provide high data rate transmission over free space channel. We report on the design of a 2×10 Gb/s-10 GHz RoFSO transmission system using the mode division multiplexing technique and evaluate its transmission performance over varying levels of dust weather conditions. The comparison of non-return to zero (NRZ) and return to zero (RZ) binary digital optical modulation techniques is carried out in the proposed system. It is found that the proposed system using NRZ modulation serves 14.5 km transmission range; however, in the case of RZ modulation, it was restricted to 10 km for a target bit error rate (BER) of 10−6, thus resulting in a noticeable link enhancement of 4.5 km. Also, we demonstrate NRZ-based MDM-RoFSO link performance and availability in dust weather conditions using the BER, maximum reachable link range, and eye diagram as key performance parameters. We obtain a reliable transmission of 20 Gb/s-20 GHz data through HG00 and HG01 channels over a link range of 2500–108 m depending on the external dust weather condition. Furthermore, since this investigation shows the feasibility of RoFSO for small size cells, which is an essential feature of 5G mobile network, the proposed system can thus be implemented as a backhaul/fronthaul link for high-band (above 6 GHz) 5G services and for providing secure transmission of biomedical sensor data.